The formation of the confessional borders between Poland, the Grand Duchy of Lithuania and Protestant duchies in the 16th century - Dmitriy Ivanovich Weber (Религия, церковь, общество, 2015)
The article discusses the phenomenon of confessional change of borders between Poland, Grand Duchy of Lithuania on the one hand and Protestant duchies on the other. The focus is on the formation of the Duchy of Courland and Semigalia as a result of the secularization of the Teutonic Order’s possessions in Prussia and Livonia. In the first half of the 16th century there were not only political, but also religious changes in the Baltics that were associated with the spread of Protestantism in the region. The new confessional borders were made between protestant duchies and Catholic Poland and the Grand Duchy of Lithuania. This process is considered through the Borderland theory. It including two types theories — boundary theory and border theory. Border theory focuses on the border as the “demarcation line” both politically and socially. In contrast with it the boundary theory, formed in the movement of cultural studies not so much physical as mental and cultural characteristics of borderlands. However, boundary-studies refers to the existence of certain cultural differences surrounding regions. One of the used approaches in this article was the concept so-called “Kulturtranfer”. This allows to consider the impact of the role of the preachers of the Holy Roman Empire in the spread of Protestantism in the Baltic region.